PERANCANGAN SISTEM PELAYANAN KESEHATAN (SIYANA) PADA PUSKESMAS MENSIKU DESA BINJAI HULU KABUPATEN SINTANG KALIMANTAN BARAT - Dedi Saputra; Windi Irmayani; Martias Martias (Jurnal Mantik Penusa)
Puskesmas Mensiku Binjai Hulu Village, located in the district of Sintang, West Kalimantan Province, is one of the government health agencies. payment. The Mensiku Health Center is in the patient health care system which is where patient service data is still recorded and stored in books which results in frequent errors in recording patient data. For this reason, the author tries to design a health service system (Siyana) at the Community Health Center to support me in the village of Binjai Hulu, Sintang, which until now has not been computerized. The design of this system is one of the good solutions to solve the existing problems at the puskesmas, thus providing faster and more effective services and also support for good patient data processing